Humanitarian Intervention from Constructivist Perspective: CaseStudy of China Peace Keeping Operation in Darfur - Rika Isnarti (AEGIS : Journal of International Relations, 2018)
Peace keeping operation as part of humanitarian intervention is a close issue to human right. It is assumed to be a way to achieve human right particularly in situation of conflict. This essay analyses the difference between humanitarian intervention and the promotion of human rights and reason state join peace keeping operation in humanitarian intervention from constructivist view? This essay chose Case study China peace keeping operation in Darfur. It concludes that Constructivism sees human rights as a norm that can be promoted by social movement as well countries accept that norm. China has to adopt human rights as one of the primary norm and join peace keeping as an idea that this country accepts the human rights norm. In this step China is a norm cascade stage. China receive human rights but still question the appropriate behavior regarding the norm. Keywords: China, Constructivist, peace keeping, norm